A History Teacher in South Korea: Teaching Elections as an Outsider. Issue 5 (3rd September 2019) - Barrow, Elizabeth; Ford, Evelyn Alex
Abstract: Teaching controversial issues can be challenging for any teacher, but especially so when the teacher is a cultural outsider. In this article, we provide a snapshot of one social studies educator's experiences teaching about two hotly contested elections—the 2016 U.S. presidential election and the 2017 Korean special election—to middle school Korean students. Each lesson brought to the forefront challenges similar to those faced in the United States but with very different outcomes, suggesting instructions that may offer solutions for social studies educators in the United States. This article provides an interesting perspective about a unique circumstance teaching social studies material in a foreign country. Additionally, this article highlights experiences teaching contested elections and provides insight into the parallel challenges social studies teachers in the United States face and how to facilitate these conversations with students.